Optimal Choices of Reconstruction Parameters United Improved C-C Algorithm and Improved G-P Algorithm - Wei, Lai; Cao, Hui; Wang, Longde (Journal of physics. Conference series, 2023)
For the phase space reconstruction of chaotic time series, the precise selection of delay and embedding dimension is indispensable. Therefore, this paper makes an in-depth study on the selection of reconstruction parameters, and puts forward some suggestions for improving the theoretical defects of the original C-C algorithm and G-P algorithm. The modified C-C algorithm optimizes the intermediate determination parameters of delay time and embedded window of the original algorithm, and makes the selection of delay time and embedded window more accurate. The improved G-P algorithm optimizes the range of neighborhood radius and the selection of scale-free interval, and improves the calculation accuracy of embedding dimension. On the theoretical basis, Lorenz sequence and Rossler sequence are used to verify, and the simulation results can be obtained. The improved algorithm can select parameters more accurately. Finally, the parameters obtained by the two improved algorithms are compared, and it is considered that the phase space reconstruction can be better by using the improved C-C algorithm to solve the delay and the improved G-P algorithm to solve the embedding dimension.